Improving food security, nutrition, incomes, natural resource base and gender equity for better livelihoods of smallholder households in sub-Saharan Africa - Pan-Africa Bean Research Alliance (2021)
This report highlights progress of achievement over the last six years 2015 – 2020 in Burundi, Zimbabwe and other PABRA countries.